Testis‐specific lactate dehydrogenase is expressed in somatic tissues of plateau pikas. Issue 1 (4th February 2013) - Wang, Duowei; Wei, Lian; Wei, Dengbang; Rao, Xinfeng; Qi, Xinzhang; Wang, Xiaojun; Ma, Benyuan
Abstract : LDH‐C4 is a lactate dehydrogenase that catalyzes the interconversion of pyruvate with lactate. In mammals the, Ldh‐c gene was originally thought to be expressed only in testis and spermatozoa. Plateau pika ( Ochotona curzoniae ), belonging to the genus Ochotona of the Ochotonidea family, is a hypoxia tolerant mammal living at 3000–5000 m above sea levelon the Qinghai‐Tibet Plateau. We found that the expression pattern of six LDH isoenzymes in the somatic tissues of female and male plateau pikas to be the same as those in testis and sperm, suggesting that LDH‐C4 was expressed in somatic tissues of plateau pika. Here we report the detection of LDHC in the somatic tissues of plateau pika using RT‐PCR, Western blotting and immunohistochemistry. Our results indicate that Ldh‐c mRNA is transcribed in the heart, liver, lung, kidney, brain, skeletal muscle and testis. In somatic tissues LDHC was translated in the cytoplasm, while in testis it was expressed in both cytoplasm and mitochondria. The third band from cathode to anode in LDH isoenzymes was identified as LDH‐C4 . The finding that Ldh‐c is expressed in both somatic tissues and testis of plateau pika provides important implications for more in‐depth research into the Ldh‐c function in mammals.